Update on biology and treatment of T-cell acute lymphoblastic leukaemia. Issue 1 (February 2015) - Patrick, Katharine; Vora, Ajay
<x xml:space="preserve">Abstract</x> Purpose of review In this article, new insights into the clinical and biological features of paediatric T-lineage acute lymphoblastic leukaemia (ALL) and their impact on treatment outcome have been described. Recent findings T-lineage ALL has considerable phenotypic and biological heterogeneity. Compared with B-lineage ALL, the prognostic significance of the presenting white cell count is weaker and the rate of decline in minimal residual disease is slower in patients with T-lineage ALL. Contemporary, response stratified, treatment protocols incorporating dexamethasone have been associated with significant improvements in outcomes and demonstrated that cranial radiotherapy is not essential for preventing central nervous system relapse. Relapse risk remains higher than for B-lineage ALL and outcome after relapse is poor. Early T-precursor phenotype and genetic abnormalities such as activating ABL1 fusions, NOTCH1/FBXW7, and cytosolic 5'-nucleotidase II gene mutations identify patient groups who may benefit from alternative treatment. New agents such as nelarabine, bortezomib, and clofarabine may be effective in preventing unsalvageable relapses identified by slow response to first-line therapy. Summary Around 85% of children and young people with T-lineage ALL are cured by current therapy. Further improvements in outcome can be expected from genetic profile and response-targeted therapeutics.